ChemInform Abstract: A New Enantioselective Synthesis of (S)‐2‐Ethoxy‐3‐(4‐hydroxyphenyl)propanoic Acid Esters (EEHP and IEHP), Useful Pharmaceutical Intermediates of PPAR Agonists. Issue 40 (30th September 2014) - Mujahid, M.; Kunte, S. S.; Muthukrishnan, M.
Abstract The new enantioselective approach to the title compounds (IV) is based on the formation of key intermediate (III) from commercially available racemic epoxide (I).